IMPACT OF THE CORONAVIRUS PANDEMIC ON THE LIVING STANDARDS OF THE POPULATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the impact of the coronavirus pandemic on the standard of living of the population. The main problems and ways of solving this problem are identified.